Analisis Segmentasi Pelanggan Dengan RFM Model Pada Pt. Arthamas Citra Mandiri Menggunakan Metode Fuzzy C-Means Clustering - Wiratama Ahsani Taqwim; Nanang Yudi Setiawan; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
PT. Arthamas Citra Mandiri is a money changer company. The company has not applied CRM (Customer Relationship Management) so that company still applying the same service to all customers. Some customers often have transactions, but on the other sides, some customers are rarely. The data used in this research is the transaction history from January 2017 until December 2017 and it including 981 transactions. Segmentation is a process to identify customers so it can help us to know the profitable customers for the company. The characteristics of the customers could be seen from RFM (Recency, Frequency, Monetary) which means Recency (the last customer transaction), Frequency (the number of transactions), and Monetary (the amount of money spend). One of the clustering methods that can be used in this research is Fuzzy C-Means. Elbow method is used to help the researcher determine the best cluster for Fuzzy C-Means. Partition Coefficient and Euclidean Distance are validation methods to knowing the best cluster. In this research, cluster 3 is the best results. Cluster results are visualized by the dashboard with some graphics which contains segmentation customer based on RFM value of PT. Arthamas Citra Mandiri customers transactions. Dashboard visualization is given to the company and researcher doing usability testing to know the effectiveness of the dashboard visualization. The results of the usability testings are 77.5. It means the dashboard is an acceptable categorized or can be accepted by the company.